Faktor Yang Berhubungan Dengan Kecemasan Ibu Hamil Trimester Iii Di Wilayah Kerja Puskesmas Beruntung Raya Banjarmasin - Setiawati, Erni; Rumilawaty, Rumilawaty; Zakiah, Zakiah (Jurnal Skala Kesehatan, 2023)
Background : anxiety during pregnancy occurs around 8-10%, and increases to 13% before delivery. This percentage can increase during the COVID-19 pandemic, especially for pregnant women who need care while staying in the hospital. Anxiety experienced by pregnant women can have an impact on pregnant women and also the baby they are carrying. The impact that can occur on the mother in the form of hypertension, prolonged labor, miscarriage and if it continues until post partum can cause the mother to experiencebaby blues, while the impacts that can occur in infants are asphyxia, caput succedaneum, and prematurity. Several factors related to the anxiety of pregnant women include age, education, husband's support, and family support Objective: To determine the factors associated with anxiety in third trimester pregnant women in the Working Area of ​​the Lucky Raya Banjarmasin Health Center Method: The design of this research is quantitative analytic, with a designCross Sectional. The population and sample were third trimester pregnant women in the working area of ​​the Lucky Raya Health Center, totaling 63 people. Statistical test using the chi square test Results: 73% of pregnant women experience anxiety, 84% aged 20-35 years, 46% receive positive support from family, 60.3% with parity 2-3, 66.7% pregnant women do not work , and 71.4% with secondary education. There is a significant relationship between age, family support, and parity with anxiety in third trimester pregnant women